A herança da política do branqueamento no processo de identidade do afrodescendente no Estado de Roraima - Fernandes, Maria Aparecida Ferreira Barbosa (Universidade do Vale do Rio dos Sinos, 2017)
This research highlights the process of Afrodescendant identity, within the framework of the formal educational process, starting from the following question, how does the construction of Afrodescendant identity in a perspective of multicultural belonging in the social context of Roraima take place? In order to answer this question, it was necessary to analyze the existing mechanisms regarding the money laundering policy and its interference in the identity processes of Afro-descendants in a perspective of multicultural belonging in Boa Vista-Roraima. In this study, Antonio Gramsci, Florestan Fernandes, Kabengele Munanga, Stuart Hall, José Ivo Follmann, Néstor García Canclini and Zygmunt Bauman are the theoretical contributions. Through the analysis of the documents and the speeches of the participants in the institutions involved in the research, it was found in this sense that the school educational environment emphasizes the symbolic representations and socially constructed concepts represented through signs and language, the identity and the Afrodescendent differences in the Temporal context in Boa Vista / Roraima, contained in social relations, which still tries to prevail white hegemony.
Keywords: Identidade; Afrodescendente; Negritude; Branqueamento; Ambiente escolar; Identity; Afrodescendant; Blackness; Bleaching; School environment; ACCNPQ::Ciências Humanas::Sociologia